(untitled) (West African Journal on Sustainable Development, 2024)
Sustainable waste management aims to keep materials in use for as long as possible and minimize the amount of solid waste that is disposed of in landfill or through incineration. Sustainable waste management relies on the waste management hierarchy, a system that focuses on avoidance, reduction, reuse, recycling, energy recovery, and finally, treatment or disposal. Here, we look at how the waste management hierarchy is central to sustainable waste management. It involves several strategies which include avoiding and reducing the amount of waste generated by maximizing efficiency and reducing consumption, Purchasing products that can be reused or repaired, as well as education around how to reuse waste products, Recycling of materials and avoiding the need to extract virgin resources as well as negating some of the negative impacts of simply disposing of waste, Energy recovery, which is the conversion of waste into usable heat, electricity, or fuel such as biogas, Treatment or disposal means landfills or incineration without energy recovery. Simple ways to start implementing sustainable waste management in homes and businesses would include scraping or replacing single-use items with reusable ones, switching as much paperwork as possible to digital versions, offering a trash alternative by providing recycling and compost bins alongside regular trash and having services to properly manage this waste. A business can also donate any materials that would otherwise go to waste to improve sustainability. Waste management can be sustainable in both businesses and homes if the right framework is implemented. But more importantly, the consequences, if waste is left unchecked, are too great not to consider.